Resonance properties of Ag-ZnO nanostructures at terahertz frequencies - Sanchez, John E. (Opt Express, 2015)
Nanoantennas have been fabricated by scaling down traditional antenna designs using nanolithographic techniques and testing them at different optical wavelengths, these particular nanoantennas have shown responses in a broad range of frequencies going from visible wavelengths to the range of the terahertz. Some self-assembled nanostructures exist that exhibit similar shapes and properties to those of traditional antenna structures. In this work the emission and absorption properties of self-assembled nanostructures made of zinc oxide nanorods on silver nanowires, which resemble traditional dipole antennas, were measured and simulated in order to test their antenna performance. These structures show resonant properties in the 10-120 THz range, with the main resonance at 60 THz. The radiation pattern of these nanostructures was also obtained by numerical simulations, and it is shown that it can be tailored to increase or decrease its directivity as a function of the location of the energy source of excitation. Experimental measurements were performed by Raman spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR) in order to show existing vibrational frequencies at the resonant frequencies of the nanostructures, measurements were made from ~9 to 103 THz and the results were in agreement with the simulations. These characteristics make these metal-semiconductor Ag/ZnO nanostructures useful as self-assembled nanoantennas in applications such as terahertz spectroscopy and sensing at terahertz frequencies.